Anna Akhmatova and the Pushkin Commission of the USSR Academy of Sciences - Alexey Yu. Balakin; Vladimir V. Turchanenko (Литературный факт)
Anna Akhmatova’s participation in the guild of Pushkin scholars consists not only of her profound and absolutely professional articles about Pushkin, but also of her direct involvement in the institutional work of Russian Pushkin scholars. The proposed article problematizes Akhmatova’s relationships with representatives of academic Pushkin studies in the 1930s–1960s. Using archival material (including documents from A.A. Akhmatova’s personal collection in the OR RNB), the authors reconstruct the history of one of the crucial Russian humanitarian academic institutions, i. e., the Pushkin Commission of the USSR Academy of Sciences in the 1940s–1950s, while simultaneously filling in the “blank spots” in Akhmatova’s biography. Particular attention is paid to identifying evidence of her personal contacts with D.P. Yakubovich, Yu.G. Oksman, and V.V. Vinogradov. For the first time, the article presents the personal compositions of the Pushkin Commission (1945 and 1958), the letter of T.G. Tsyavlovskaya to Akhmatova from March 1934, dedicated to the work on the volume “By Pushkin’s Hand,” and other materials for the biography of Anna Akhmatova, and provides comprehensive information on the materials of the Pushkin Commission and the sector (group) of Pushkin studies, deposited in Akhmatova’s personal archival fund. The article ends with the attribution of a group photo portrait.